Implikasi Hospital By Law - Teguh Sunartejo (Perspektif Administrasi Publik dan hukum, 2024)
Health as one of the most important factors for the realization of welfare is the ideal of Indonesian state law. The role of the rule of law was to realize this philosophical goal when the 1945 Constitution of the Republic of Indonesia (UUD 1945) was amended in 1945 and Health Law No. 36 was promulgated in 2009. The history of the development of hospitals in Indonesia was first established in 1626. Hospital Bylaws are regulated by Law Number 44 of 2009, specifically Article 29 paragraph (1) letter r which requires Hospital Bylaws, technically guided by Kepmenkes Number 772/Menkes/SK/VII/2002 concerning Guidelines for Hospital Internal Regulations (Hospital Bylaws) and Permenkes Number 755/Menkes /Per/IV/2011 concerning Organizing Medical Committees in Hospitals. Hospital Bylaws include Corporate Bylaws and Medical Staff Bylaws which are the Legal Implications of "Hospital By Laws" Hospital Internal Regulations.